An empirical model of medicare costs: The role of health insurance, employment, and delays in medicare enrollment - Yuanyuan Deng; Hugo Benítez-Silva (Econometrics, 2021)
Medicare is one of the largest federal social insurance programs in the United States and the secondary payer for Medicare beneficiaries covered by employer-provided health insurance (EPHI). However, an increasing number of individuals are delaying their Medicare enrollment when they first become eligible at age 65. Using administrative data from the Medicare Current Beneficiary Survey (MCBS), this paper estimates the effects of EPHI, employment, and delays in Medicare enrollment on Medicare costs. Given the administrative nature of the data, we are able to disentangle and estimate the Medicare as secondary payer (MSP) effect and the work effects on Medicare costs, as well as to construct delay enrollment indicators. Using Heckman's sample selection model, we estimate that MSP and being employed are associated with a lower probability of observing positive Medicare spending and a lower level of Medicare spending. This paper quantifies annual savings of 5.37 billion from MSP and being employed. Delays in Medicare enrollment generate additional annual savings of 10.17 billion. Owing to the links between employment, health insurance coverage, and Medicare costs presented in this research, our findings may be of interest to policy makers who should take into account the consequences of reforms on the Medicare system.
Keywords: 330; delays in Medicare enrollment; employer-provided health insurance; Heckman's sample selection model; Medicare as secondary payer; Medicare cost